Acute toxicity and environmental risk of teflubenzuron to Daphnia magna, Poecilia reticulata and Lemna minor in the absence and presence of sediment - Medeiros, Louise S. [UNESP]; Souza, Jaqueline P.; Winkaler, Elissandra U.; Carraschi, Silvia P. [UNESP]; Cruz, Claudinei [UNESP]; Souza-Júnior, Severino C. [UNESP]; Machado-Neto, Joaquim G. [UNESP] (Taylor & Francis, 2013)
This study aimed to estimate the acute toxicity of teflubenzuron (1-(3,5-dichloro-2,4-difluorophenyl)-3-(2,6-difluorobenzoyl)urea) (TFB) for Daphnia magna, Lemna minor and Poecilia reticulata, in the absence and presence of sediment; evaluate the effect of sediment on the TFB bioavailability; and to classify this insecticide according to its environmental poisoning risk for agricultural and aquaculture uses. The tests of TFB acute toxicity were conducted in static system in a completely randomized design with increasing TFB concentrations, and a control group. The TFB has been classified according to the estimated values of EC50 and LC50 by its acute toxicity and environmental risk. The sediment significantly reduced toxicity and bioavailability of TFB in water column. Therefore, the insecticide can be classified as being highly toxic to Daphnia magna, which means the agricultural and aquacultural uses of TFB pose a high risk of environmental toxicity to non-target organisms. However, it was practically non-toxic to L. minor and P. reticulata. © 2013 Copyright Taylor and Francis Group, LLC.
Keywords: Ecotoxicity; environmental risk; fish; insecticide; macrophyte; microcrustacean; Completely randomized designs; Environmental risks; Environmental toxicity; Macrophytes; Non-target organism; Poecilia reticulata; Agriculture; Biochemistry; Fish; Insecticides; Risk perception; Sedimentology; Sediments; Urea; Toxicity; benzamide derivative; teflubenzuron; aquaculture; bioavailability; concentration (composition); poisoning; sediment; toxicity; water column; animal; Araceae; Daphnia; drug effect; growth, development and aging; LD 50; Poecilia; water pollutant; Animals; Benzamides; Geologic Sediments; Lethal Dose 50; Water Pollutants, Chemical